Causes of development of cicatrical laryngeal stenosis - M. A. Ryabova; E. E. Posobilo (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
There is the retrospective analysis of cicatrical laryngeal stenosis causes in the patients who were treated in the ENT Department First Pavlov State Medical University of St. Petersburg from 1992 to 2003 and from 2003 to 2013.